ENHANCING SPEAKING SKILL THROUGH WASTE OF MACHINE’S SPARE PARTS AS THE LEARNING MEDIA - Yuliana Ningsih; Kurnia Dwi Artika (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
The study investigated whether the machine's spare parts' waste impacts teaching, especially enhancement the students' speaking skills, and describes how the waste of machine's spare parts influences the students' speaking skills. The study explored the waste of machine's spare parts, which has a negative impact on the environment, to create a learning media to enhance speaking skills to the students of Politeknik Negeri Tanah Laut, Mechanical Engineering majoring. Action research was implemented in two cycles, and the data were collected through observation, questionnaire, and speaking assessment. Pre-Test Testing, Cycle I Test, and Cycle II Test use the same speaking test used waste of the machine's spare parts by students. The data showed that the mean score of the Pre-test was 65,45, 70,1 in Cycle I, and 82 in Cycle II. Therefore, it can be concluded that the use of machine’s spart waste can improve students’ speaking skill. In addition, the finding also showed that it gives enhancement to students' participation and confidence in speaking English.Keywords: waste of machine’s spare part, speaking skill, learning media